The Influence Of Workload, Work Environment, And Facilities On The Performance Of Healthcare Workers At The Bintuni Public Health Center In Bintuni District, Teluk Bintuni - St. Subaedah; Andi Mappatompo Badawi; Samsul Rizal (Green Publisher Indonesia, 2024)
This study aimed to determine, analyze, and describe the influence of workload, work environment, and facilities on the performance of health workers at Bintuni Health Center, Teluk Bintuni Regency, using multiple linear regression analysis techniques. This research was quantitative in nature, employing a questionnaire as the data collection instrument. The study involved 97 respondents comprising health workers at Bintuni Community Health Center. The results indicated that workload had a significant negative influence on the performance of health workers with P = 0.000 < 0.05 and a coefficient value of -0.340. The work environment had a significant positive influence on performance with P = 0.000 < 0.05 and a coefficient value of 0.243, while facilities had a significant positive influence with P = 0.000 < 0.05 and a coefficient value of 0.406. Therefore, higher workload could decrease the performance of health workers, where as a good work environment and facilities would enhance the performance of health workers at Bintuni Community Health Center.